Evaluation of the impact of Shigella virulence genes on the basis of clinical features observed in patients with shigellosis - Visnu Pritom Chowdhury; Ishrat Jahan Azmi; Md Ahshanul Haque; Mohammad Rafiqul Islam; Mahmuda Akter; Shahin Mahmud; Abu Syed Golam Faruque; Kaisar Ali Talukder (Journal of Infection in Developing Countries)
Introduction: Shigella continues to cause significant morbidity and mortality each year, mostly in under-five children living in developing countries. We investigated the association between Shigella virulence genes and shigellosis.